2021
DOI: 10.1037/cep0000257
|View full text |Cite
|
Sign up to set email alerts
|

From lollipops to lidocaine: The need for a universal print-to-speech framework.

Abstract: Objective: There is a strong relationship between reading and articulation (Lervåg & Hulme, 2009; Pan et al., 2011). Given the tight coupling of these processes, innovative approaches are needed to understand the intricacies associated with print-speech connections. Here we ran a series of tightly controlled experiments to examine the impact of mouth perturbations on silent reading. Method: We altered the mouth, via somatosensory feedback, in several ways: (a) a large lollipop in the mouth (E1), (b) a candy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
(84 reference statements)
0
1
0
Order By: Relevance
“…First, it is important to note that the lack of difference between the groups does not mean that the somatosensory feedback does not continue to play a notable role in reading processes. For example, we recently showed that certain somatosensory perturbations (e.g., large lollipops and lidocaine) can actually facilitate reading performance for skilled readers (Cummine et al., 2021). Thus, it may be that these regions are functionally connected to a greater degree than they are structurally connected.…”
Section: Discussionmentioning
confidence: 99%
“…First, it is important to note that the lack of difference between the groups does not mean that the somatosensory feedback does not continue to play a notable role in reading processes. For example, we recently showed that certain somatosensory perturbations (e.g., large lollipops and lidocaine) can actually facilitate reading performance for skilled readers (Cummine et al., 2021). Thus, it may be that these regions are functionally connected to a greater degree than they are structurally connected.…”
Section: Discussionmentioning
confidence: 99%